(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The study was conducted at Upazila Livestock Office from 1st January to 31th March, 2010 to observe the prevalence of PPR in goat at Mirzaganj upazila in Patuakhali District. A total of 183 goats were examined based on the clinical signs and gross pathological lesions of which 92 were PPR affected makes up 50.27%. After categorizing the animals according to their breed, age and vaccination history it was revealed that Black Bengal goats were more susceptible (54.93 %) than Jamunapari (31.38 %). The prevalence of PPR was maximum 63.33% at age category of 7-12 months, in compare with 44.68%, 41.87%, 45.45% at age category of ? 6 months, 13-18 months and ? 19 months respectively. Non-vaccinated goats were more susceptible (66.40%) to PPR infection than vaccinated goats (19.56%). Parental (I/M) Oxytetracycline was more effective (64%) than parental (I/M) Sulphadimidine (44%) along with symptomatic treatment. PPR causes higher mortality and heavy economic losses in every year which may be reduced substantially by proper vaccination and other managemental approaches. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14811 J. Environ. Sci. & Natural Resources, 5(2): 181-184 2012